Clinicoepidemiologic profile of inguinal hernia in rural medical college in central India - S Siddharth Rao; Prashant Singh; Dilip Gupta; Ravinder Narang (Wolters Kluwer Medknow Publications, 2016)
Background: Inguinal hernias are one most common problem dealt by general surgeons and have significant morbidity and mortality. In the developed countries, almost all of the inguinal hernias are recognized early and present early in the course of disease to the surgeon. However, in developing countries, quite a considerable percentage of it is not repaired leading to a higher incidence of morbidity and mortality. Hence, we planned this study to understand the clinicoepidemiologic profile of inguinal hernia in rural medical college in central India. Methodology: This is a descriptive epidemiological, prospective study carried out in rural medical college. All patients who presented to the surgical wards and outpatient with a clinical diagnosis of inguinal hernia were included in the study. Results: Among the 61 patients included in the study, most of them were men (91.8%) with a mean age of 45.02 ± 22.87 years, married (77.05%) and farmer (37.7%) by occupation. All the patients of inguinal hernia presented with the complaints of lump above the inguinal crease and three-fourth of these patients had complaints of pain (73.77%) and had predominantly right-sided hernia. More than half of the patients had one of the signs of obstruction at the time of presentation of which crease in pain was the most common (52.46%). Most of the patients presented late to the hospital due to the lack of awareness of the disease. The most common operative procedure done was open hernioplasty (Lichtenstein's procedure) in 61.67% patients followed by herniotomy (18.33%) and herniorrhaphy (modified Bassini's procedure) in 13.33% patients. Conclusion: Late presentation of disease is the hallmark of this disease in rural areas due to the lack of awareness. Increasing awareness of the disease among general population will lead to inguinal hernias being detected at earlier stage and will decrease the morbidity due to this disease.